(untitled) (Archives of Mechanics - Test, 2003)
The electroelastic response of a penny-shaped crack in a piezoelectric cylinder of finite radius is investigated in this study. Fourier and Hankel transforms are used to reduce the problem to the solution of a pair of dual integral equations. They are then reduced to a Fredholm integral equation of the second kind. Numerical values of the stress intensity factor, energy release rate and energy density factor for piezoelectric ceramics are obtained to show the influence of applied electrical loads.